Cryopyrin‐associated periodic syndrome in Australian children and adults: Epidemiological, clinical and treatment characteristics. (20th September 2016) - Mehr, Sam; Allen, Roger; Boros, Christina; Adib, Navid; Kakakios, Alyson; Turner, Paul J; Rogers, Maureen; Zurynski, Yvonne; Singh‐Grewal, Davinder
Abstract : Aim: Cryopyrin‐associated periodic syndromes (CAPS) encapsulate three auto‐inflammatory conditions, ranging in severity from mild (familial cold auto‐inflammatory syndrome: FCAS), moderate (Muckle‐Wells syndrome: MWS) and severe (neonatal onset multi‐inflammatory disorder: NOMID). We aimed to describe the epidemiology, clinical features and outcomes of Australian children and adults with CAPS. Methods: Patients were identified and clinical data collected through a questionnaire sent during 2012–2013 to clinicians reporting to the Australian Paediatric Surveillance Unit and subscribing to the Australasian Societies for Allergy/Immunology, Rheumatology and Dermatology. Results: Eighteen cases of CAPS were identified (8 NOMID; 8 MWS, 2 FCAS); 12 in children <18 years of age. The estimated population prevalence of CAPS was 1 per million persons. Diagnostic delay was frequent, particularly in those with milder phenotypes (median diagnostic delay in MWS/FCAS 20.6 years compared with NOMID 2.1 years; P = 0.04). Common presenting features included urticaria (100%), periodic fever (78%), arthralgia (72%) and sensorineural hearing loss (61%). Almost all (90%) MWS patients had a family member similarly affected compared with none in the NOMID group ( P = 0.004). A significant proportion of patients on anti‐interleukin (IL)‐1 therapy ( n = 13) no longer had systemic inflammation. Only 50% with sensorineural hearing loss had hearing restored on anti‐IL‐1 therapy. Conclusions: Although CAPS are rare, patients often endured prolonged periods of systemic inflammation. This is despite almost all MWS patients having family members with similar symptoms and children with NOMID presenting with chronic infantile urticaria associated with multi‐system inflammation. Hearing loss in NOMID/MWS was frequent, and reversible in only 50% of cases.